Prevalence of Tooth Transposition among Pakistani Population (Medical Forum Monthly, 2024)
Objective: The objective of this study was to determine the prevalence of tooth transposition among Pakistani populationStudy Design: Observational / descriptive studyPlace and Duration of Study: This study was carried out in the Department of Orthodontics Karachi Medical and College, Karachi from September 2013 to April 2014.Materials and Methods: This study was done with panaromic radiographs of 530 subjects (210 males, 320 females). For each patient variables like age, sex, presence of tooth transposition, type, location and classification of tooth transposition.Results: Tooth transposition was found in 09 subjects (1.69%) (8 females and 1 male). The most commonly involved transposition was found was found in Maxillary canine and lateral incisor ( 66.67 %).The frequency of complete transposition was 30% (3 out of 10) , it was found more on left side than right side( 7/3).all transpositions were found in maxilla.Conclusion: The tooth transposition was found in 1.69% in a sample of Pakistani population and transposition between upper canine and lateral incisor was the most commonly observed transposition.